Online feedback system / Anusha Devi Rajaratnam - Anusha Devi , Rajaratnam (2004)
Currently, FSKTM, and many other universities as well, conducts manual course-end surveys in which each student will have to complete a paper survey form to evaluate each of the courses they have taken during a particular semester. This Online Feedback System is designed to automate this manual survey process by putting the entire evaluation system online. Students can login to take the survey through a Web interface, results are retained in a database, and survey statistics can be accessed on the Website. The objective of this system is to develop a system that enables the students to take this survey from any remote location that has an Internet connection. This project will focus on three modules which are Administrator module, Lecturer module and Student module. Administrator has the authority to create or modify questions, where as the lecturers will be able to view and print report according to course code, semester and instructors name Students will select categories such as department, course code, year/ year graduated, view and give feed back The web server for this system is the Internet Information Server (IIS) running under the Microsoft Windows 2000. Active Server Pages (ASP) will be the main programming language technology while database will be created and stored from Microsoft Access base on the system requirement.